Comparisons of buckling capacity curves of pressurized spheres with EDR provisions and experimental results = Porównanie krzywych nośności wyboczeniowej powłok sferycznych obciążonych ciśnieniem z zaleceniami EDR oraz z wynikami badań eksperymentalnych - Błażejewski, Paweł; Marcinowski, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Existing provisions leading to the assessment of the buckling resistance of pressurised spherical shells were published in the European Design Recommendations (EDR). This book comprises rules which refer to the stability of steel shells of different shapes. In the first step of the general procedure they require calculation of two reference quantities: the elastic critical buckling reference pRcr and the plastic reference resistance pRpl.
Keywords: steel spherical shells; buckling resistance; FEM; numerical approach; capacity curve; powłoka sferyczna; nośność wyboczeniowa; MES; analiza numeryczna; krzywe nośności wyboczeniowej